Mechanically flexible viscosity sensor for real‐time monitoring of tubular architectures for industrial applications. Issue 3 (25th October 2020) - Nour, Maha A.; Khan, Sherjeel M.; Qaiser, Nadeem; Bunaiyan, Saleh A.; Hussain, Muhammad M.
Abstract: Real‐time monitoring of fluid viscosities in tubular systems is essential for industries transporting fluid media. The available real‐time viscometers for tubular systems have major drawbacks, such as using invasive methods with large pressure drops due to flow disturbances, destructive installation processes with permanent tube damage, and limited operability with laminar flows. Therefore, developing a viscometer to address the above‐mentioned concerns is required for industrial applications. In this study, a new application of a velocity‐dependent viscometer using a novel design for real‐time measurements with insignificant flow disruption is proposed. It involves a Poly (methyl‐methacrylate) microchannel bridge with a microfluidic flowmeter attached to a mechanically flexible Polydimethylsiloxane platform connected to the inner surface of the pipe, which can adapt to different pipe diameters and curvatures. Moreover, the proposed viscometer uses the pipe flow driving force to flow fluids into the microchannel for measurement without requiring a pumping system or any sample withdrawals. The results of the simulation analysis match the experimental results of the sensor performance. The sensor can measure different viscosities in the range of 4‐334 mPa s with a resolution higher than 2.7 mPa s. Finally, a stand‐alone system is integrated with the sensor for wireless data transmission. Abstract : A microfluidic viscometer that depends on the flow rate change is developed for real‐time monitoring of fluids in the pipe systems. The standalone system is capable of measuring different fluid viscosities over a wide range from 4 to 334 mPa s with resolution better than 2.7 mPa s.